Hydrochlorothiazide use, sun exposure, and risk of keratinocyte cancer - Jeffrey J. VanWormer; Eseoghene B. Abokede; Richard L. Berg (BMC, 2022)
Abstract Background Keratinocyte cancer (KC) rates are increasing in the U.S., particularly in older age groups. Use of hydrochlorothiazide (HCTZ), due to its photosensitizing properties, and high sun exposure are two known NMSC risk factors, but their synergistic effects are undetermined. The purpose of this study was to examine the development of NMSC between adults who did and did not use HCTZ, as well as those with high and low sun exposure. Methods A retrospective case-control sample was assembled from adult patients in north-central Wisconsin (USA). Duration of HCTZ use and occupational sun exposure were extracted from electronic health records, along with a linked survey of lifetime sun exposure. Results There were 333 cases and 666 controls in the analytical sample. A significant main effect was observed for HCTZ duration in the full sample. Under low sun exposure, the odds of NMSC was 14% greater for each additional year of HCTZ use (aOR = 1.14 [1.11, 1.18], p < 0.001). In a sensitivity analysis of participants age 70 years and over, there was a borderline significant (p = 0.086) HCTZ use by high sun exposure interaction, suggesting modestly increased HCTZ risk in older, high sun exposure adults. Conclusions Consistent with prior studies, longer duration of HCTZ use was a predictor of NMSC in north-central Wisconsin adults. NMSC may be accelerated in HCTZ users with outdoor lifestyles, but future studies should attempt to further disaggregate specific effects of sun exposure time, HCTZ duration, and age on NMSC development.